2014
DOI: 10.4236/nr.2014.55017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>γ</i>-Valerolactone Blending on Engine Performance, Combustion Characteristics and Exhaust Emissions in a Diesel Engine

Abstract: γ-valerolactone (GVL) is a C5-cyclic ester that can be produced from biomass providing a potentially renewable fuel for transportation and feedstock for the chemical industry. Experiments were performed with fossil diesel (D), D + biodiesel (BD) and D + BD + GVL blends. A four-cylinder, turbocharged direct injection diesel engine was used for the tests. The engine was coupled to a dynamometer to vary the load. CO, NO x , THC and smoke emissions were measured by using a multi-channel gas analyzer. Combustion ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 35 publications
0
44
0
1
Order By: Relevance
“…The standard procedure based on fitting vapor pressure (p s ) and liquid density data (ρ) was used. An optimization procedure utilizing the following objective function was used (6) where N ρ and N ρ s are numbers of experimental points. w ρ,i and w ρ s ,j are statistical weights of experimental data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The standard procedure based on fitting vapor pressure (p s ) and liquid density data (ρ) was used. An optimization procedure utilizing the following objective function was used (6) where N ρ and N ρ s are numbers of experimental points. w ρ,i and w ρ s ,j are statistical weights of experimental data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3 million tonnes. LA can be reduced to 4‐hydroxyvaleric acid that readily cyclizes via intramolecular dehydration to γ‐valerolactone (GVL), which has been considered as a sustainable liquid and can be used for the production of fuels, fuel additives, fine chemicals and utilized as a solvent or lighter fluid . Consequently, a robust synthesis of LA from cheap and readily available biomass residues is highly desired opening an alternative utilization of large scale formed carbohydrate rich biomass wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Solely the vapor pressure of the GVL/gasoline blend was lower than that of the ethanol/gasoline blend. Bereczky et al [4] investigated the influence of blending GVL into diesel and bio-diesel in a four-cylinder, unmodified diesel engine. They found that engine performance and NO x -emissions remained unchanged, but carbon monoxide, unburned fuel, and soot emissions were significantly reduced.…”
Section: Introductionmentioning
confidence: 99%